2018
DOI: 10.1186/s12915-017-0472-5
|View full text |Cite
|
Sign up to set email alerts
|

A role for endothelial nitric oxide synthase in intestinal stem cell proliferation and mesenchymal colorectal cancer

Abstract: BackgroundNitric oxide (NO) has been highlighted as an important agent in cancer-related events. Although the inducible nitric oxide synthase (iNOS) isoform has received most attention, recent studies in the literature indicate that the endothelial isoenzyme (eNOS) can also modulate different tumor processes including resistance, angiogenesis, invasion, and metastasis. However, the role of eNOS in cancer stem cell (CSC) biology and mesenchymal tumors is unknown.ResultsHere, we show that eNOS was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 57 publications
0
31
0
Order By: Relevance
“…It has been reported that iNOS is highly expressed in almost 60% of human colon adenomas, whereas it is low or undetectable in normal intestinal tissues [27,45]. Interestingly, the expression level of iNOS attenuated in an advanced tumor with metastasis, and was absent in human mesenchymal CRC subtypes [46].…”
Section: Inos/nos2mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that iNOS is highly expressed in almost 60% of human colon adenomas, whereas it is low or undetectable in normal intestinal tissues [27,45]. Interestingly, the expression level of iNOS attenuated in an advanced tumor with metastasis, and was absent in human mesenchymal CRC subtypes [46].…”
Section: Inos/nos2mentioning
confidence: 99%
“…Recent studies revealed that eNOS might be involved in various tumor hallmarks, including invasion, metastasis, angiogenesis, and resistance [61,62]. Therefore, eNOS could act as a marker for poor prognosis in human cancer [46,63]. Peñarando et al explored the mechanism of eNOS in mesenchymal colorectal cancer and cancer stem cells.…”
Section: Enos/nos3mentioning
confidence: 99%
“…However, there is a huge controversy about the role of iNOS in colon cancer (Ambs et al, 1998;Moochhala et al, 1996;Peñarando et al, 2018) Treatment of colitis induced animals by CM whey reduced the expression level of iNOS gene (Fig.2). This indicates the anti-inflammatory activity of CM whey as iNOS expression was found to correlate with the severity of DSS-induced colitis (Seril et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The iNOS isoform has been shown to be the predominant enzyme that promotes tumor progression through nitrogen oxide (NO) production. Several studies indicated that the endothelial isoenzyme (eNOS) can also modulate different tumor processes including resistance, angiogenesis, invasion and metastasis (Peñarando et al, 2018;Thomsen et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Circulating NOS3 levels were signi cantly correlated with progression-free survival and overall survival (OS) of metastatic colorectal cancer patients (9). Another research in mesenchymal colorectal cancer patients reported that NOS3 upregulation occurs after Apc loss which was associated with poor prognosis (10). In breast cancer, the increasing expression of NOS3 was reported to be a pro-angiogenic factor (11).…”
Section: Introductionmentioning
confidence: 99%